(untitled) (INNOVATIVE ECONOMY, 2021)
Korneliuk O.A., Zavadska Yu.I., Chapko R.V. FORMS OF IMPLEMENTATION OF CROSS-BORDER COOPERATION IN THE EUROPEAN UNION Purpose. The purpose of the article is to study the features of the main modern forms of cross-border cooperation in the European Union, in particular, organizational forms of cross-border cooperation, historical background, and stages of cross-border cooperation, to analyse the functioning of Euro-regions at the present stage, including financial instruments, and especially the implementation of these processes in a pandemic COVID-19. Methodology of research. The study uses generally accepted methods in economics: a monographic, theoretical, and comparative analysis – to reveal the conceptual foundations of cross-border cooperation; analysis and synthesis, system-structural, abstract and logical, statistical groupings – to determine and analyse the forms of cross-border cooperation in the European Union. Findings. The main theoretical approaches to defining the essence of cross-border cooperation, its place, and its role in the process of economic development of the regions and participating countries are analysed. The main forms of implementation of cross-border cooperation are systematized, the results of cross-border cooperation are considered on the example of the functioning of separate Euro-regions and realization of cross-border projects. It is determined that in the conditions of globalization and strengthening of integration processes between the states the need to expand and deepen international relations between local self-government bodies grows. An analysis of the peculiarities of the development of cross-border cooperation in the face of the global pandemic COVID-19 was conducted. Originality. For the first time, it was established that the peculiarities of the implementation of forms of cross-border cooperation taking into account the new conditions caused by the COVID-19 pandemic, which will allow the development of an adaptive mechanism of organizational and economic support of this process. Practical value. The results of the conducted study can be used in the educational process, in particular, in the training of specialists in project management, management and administration, as well as in the implementation of practical activities of public authorities and local governments of urban settlements, cities, and regions that are cross-border regions. Key words: cross-border cooperation, forms of cross-border cooperation, Euro-region, cross-border project.